2020
DOI: 10.30682/nm2002b
|View full text |Cite
|
Sign up to set email alerts
|

Food security and migration in Africa: a validation of theoretical links using case studies from literature

Abstract: The connection between food security and migration is increasingly discussed by both international agencies and academic literature. However, despite several improvements, we continue to know little about the complex causal-effect relations that link these aspects and, in particular, how much migration patterns are affected by food security issues and how much, as a feedback, migration can affect food security, on both the origin and destination areas. This paper aims firstly to draw a general framework of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
(76 reference statements)
0
5
0
3
Order By: Relevance
“…The analysis showed that the level of food security is a discriminating factor for the clustering of countries: a clear gap emerges between the countries of Western Europe and those of the MENA area. The transition towards more sustainable food production and consumption models has also reached different stages in the various countries of the area, representing a further element of distance (Mulazzani et al, 2020). For example, the extent of food loss at various stages of the supply chain varies considerably from one region to another.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that the level of food security is a discriminating factor for the clustering of countries: a clear gap emerges between the countries of Western Europe and those of the MENA area. The transition towards more sustainable food production and consumption models has also reached different stages in the various countries of the area, representing a further element of distance (Mulazzani et al, 2020). For example, the extent of food loss at various stages of the supply chain varies considerably from one region to another.…”
Section: Discussionmentioning
confidence: 99%
“…In his paper, Dedeoğlu (2018) assessed the present condition of migrants working in agricultural production in Turkey and analyzed the employment of migrant labor in agricultural production in the context of social development in rural regions of Turkey. Mulazzani et al (2020), first aimed to outline the link between food security and migration, and then to validate it using the empirical literature from the African continent. Cento and Bahşi (2022) evaluated the situation of Syrian agricultural workers under temporary protection in Turkey from the perspective of farmers.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the lack of food security has an impact on both internal and external migration. The connection between food security and migration is increasingly discussed by both international agencies and academic literatüre (Mulazzani et al, 2020). Đokić et al (2021) states that countries with high levels of food security and political stability have the highest influx of immigrants.…”
Section: Introductionmentioning
confidence: 99%